Skeletal Muscle Haemangioma: A Cause for Chronic Pain about the Knee: A Case Report. (9th September 2012) - Kiran, Kopuri Ravi; Suresh Babu, T. V.; Babu, S. Suresh; Deepti, K.
Abstract : Skeletal muscle haemangiomas are uncommon soft tissue tumors; more than 90% are misdiagnosed initially. They present as chronic pain and swelling in a muscle with or without a history of trauma. Plain X-rays, bone scans, computerized tomography (CT) studies, and angiography studies may not always be specific for this tumor. Diagnostic ultrasound is an appropriate initial imaging modality for suspected haemangioma, although magnetic resonance imaging is the investigation of choice. Many treatment modalities for the symptomatic haemangiomas are available of which surgical excision is the most preferred. We present an unusual case of pain, swelling, and restriction of movements in the right knee following an episode of trauma in a 12-year-old boy who was being followed for 1 year by a general practioner and later referred to us. The patient was diagnosed to have intramuscular cavernous haemangioma in the vastus medialis by us for which he was treated by surgical excision and followed for 1 year and found to have no recurrence. The clinical features, radiological picture, pathological histology, diagnostic tools, and treatment options have been discussed.